Complexity of Gamification - (:unkn) unknown (My University, 2021)
This thesis introduces ideas for determining the Complexity of Gamifying the learning of a task/skill. We have taken three different tasks: Learning of L2 Languages (Non-mother-tongue languages), Learning about Food preparation and Learning of Physical exercises and applied our ideas to identify the complexity of gamifying them. To further supplement our idea, we have taken few existing popular gamified tasks by 3rd party companies and addressed the complexity of making them, using our ideas, and how adding new features to them, will increase the complexity. In summary, our work presented in this thesis is useful in practice for estimating a part of the time needed to design and develop a digital game, estimating the impact of game design on finances, and for revealing some of the gamification factors that can be controlled to meet temporal and financial constraints in the game production.